Konflik dan pengaruh budaya kerja etnik dalam kalangan kakitangan awam di pihak berkuasa tempatan Pasaman Barat, Wilayah Sumatera Barat, Indonesia - Frinaldi, Aldri (2014)
Indonesia consists of various ethnic groups. Ethnic diversity leads them practice the culture of their own ethnic work, especially in the public sector. As result there is a conflict among the work culture, especially in public sector. The main objective of this study is to examine the conflict between ethnic work culture and the public sector work culture in the local government of Pasaman Barat. The ethnic cultures studied are the Minangkabau, Mandailings and Java. This study is important because there is a culture clash between the work cultures of the public sector with the culture of the ethnic groups inherited by civil servants based on their ethnicity. The methodology adopted in this study is qualitative ethnographic method by nature. Data collection was based on the observation and in-depth interviews with the 37 informants, made up of 18 Minangkabau, 11 Mandailings and eight Javanese civil servants as well as content analysis of relevant documents. Informants of this study comprised of civil servants in local government Pasaman Barat who are Minangkabau, Mandailings and Javanese. The results of the study showed that the effect of ethnic culture is dominant in the practice of civil servants from the three ethnic groups as opposed to the work culture set by the Indonesian government. Among the factors behind these is the fact that it is easier for the civil servants to practice their ethnic work culture which has been nurtured in them for a very long time. As a result, the performance of the civil servants in providing services to the people is poor. The ethnic work culture characteristics that are dominant among the Minangkabau public servants are galie, maota, and egalitarian. Meanwhile, among the Mandailings, they are paternalistic, giot, ipas, jogal, and decisive. And for the Javanese, they are nrimo, alon-alon weton klakon, taqlid, paternalistic and conscientious. This study proposed that a systematic and continuous effort should be made to change the work culture of public servants. In addition, a positive multi-ethnic work culture should be part of the public sector work culture and transformed into civil servants in Indonesia.